TIANG MASJID KERAMAT BANUA HALAT KABUPATEN TAPIN KALIMANTAN SELATAN - Fahriah Chintya (Balai Arkeologi Kalimantan Selatan, 2008)
Masjid Keramat Banua Halat is one of ancient mosques in South Kalimantan. Masjid Keramat Banua Halat has some unique characteristis, i.e.: the existence of several pillars with people names carved in Malayu-Arabic scripts and the availability of a pillar for leaning of the corpse. This pillar is popularly mentioned as liang sandaran mayat. The people, whose names caNed on the pillars, are the people who gave funding for building the mosque. Some of the scripts are written in golden ink and placedÂ either on base or other part of the mosque pillars which are decorated with pucuk rabung motifs. On the other hand, the corpse pillar is plain without any decoration, black in colour, and made of ulin wood (Eusideroxylon Zwagerii)) flakesblack in colour, and made of u/in wood (Eusideroxylon Zwagerii) flakes.